Protective Effects of Ethanolic Extract of Curcuma longa (Turmeric) on Sperm Quality and Testicular Histology Following Lead Acetate-Induced Testicular Toxicity in Adult Male Wistar Rats - Elizabeth Obioma Nweke; Emmanuel Chimagoziwom Prince; A. U. Obi; Tochukwu Miracle Nweke (Health Science Research International, 2026)
Background: Lead acetate is an environmental toxicant associated with impaired male reproductive function. Curcuma longa (turmeric), particularly its bioactive compound curcumin, possesses antioxidant and anti-inflammatory properties. This study evaluated the effects of ethanolic C. longa extract on sperm quality and testicular histology following lead acetate-induced testicular toxicity in adult male Wistar rats. Methods: Twenty-five adult male Wistar rats were randomly assigned into five groups (n = 5). Group A served as control; Group B received lead acetate (60 mg/kg); Group C received ethanolic C. longa extract (100 mg/kg); and Groups D and E received lead acetate (60 mg/kg) with 200 and 400 mg/kg C. longa extract, respectively. Treatments were administered orally for four weeks. Sperm motility, total sperm count, morphology, and testicular histology were assessed. Data were analyzed using one-way ANOVA followed by Bonferroni post-hoc test at p < 0.05. Results: Lead exposure reduced active motile sperm (72.50 ± 1.44%) compared with control (82.50 ± 1.44%) and increased non-motile sperm (27.50 ± 1.44% vs. 17.50 ± 1.44%). Total sperm count decreased from 66.90 ± 0.80 to 59.30 ± 7.50 × 10⁶/ml. The 200 mg/kg co-treated group showed 80.00 ± 2.88% active motile sperm and the highest total sperm count (72.70 ± 0.40 × 10⁶/ml). The extract-only group showed the lowest motility and sperm count and highest abnormal morphology. Histologically, lead exposure altered seminiferous architecture, while extract-only treatment produced severe degeneration and spermatogenic arrest. Co-treated groups showed partial preservation, although abnormalities persisted. Conclusion: Ethanolic C. longa extract produced variable effects on sperm quality and testicular histology following lead exposure, with some favorable changes particularly at 200 mg/kg. However, persistent abnormalities indicate that these effects were not uniformly dose-dependent. Further mechanistic studies are warranted.